Exploring the meaning of lecturer leadership management in nursing education: A phenomenological approach - Edison Kabak (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Leadership is an important competency in nursing education, but students' experience in understanding lecturer leadership management is still rarely explored. Purpose: To understand students' experiences related to lecturer leadership management in nursing education. Method: A phenomenological approach was employed with in-depth interviews with 12 students as participants. The data was analyzed thematically to identify the experiences and meanings gained by students related to lecturer leadership. Results: The analysis showed four main themes: (1) lecturers as role models in leadership management, (2) guidance and mentoring in the leadership process, (3) open communication and interaction in leadership management, and (4) instilling ethical and leadership values by lecturers. Students assess direct interaction with lecturers, practical experience, and intensive mentorship as important factors in the development of professional leadership competencies. Conclusion: Student experiences confirm that lecturer leadership management shapes the professional understanding, skills, and values applied in nursing practice.